Functional reconstruction of a eukaryotic-like E1/E2/(RING) E3 ubiquitylation cascade from an uncultured archaeon. Issue 1 (December 2017) - Hennell James, Rory; Caceres, Eva; Escasinas, Alex; Alhasan, Haya; Howard, Julie; Deery, Michael; Ettema, Thijs; Robinson, Nicholas
Abstract The covalent modification of protein substrates by ubiquitin regulates a diverse range of critical biological functions. Although it has been established that ubiquitin-like modifiers evolved from prokaryotic sulphur transfer proteins it is less clear how complex eukaryotic ubiquitylation system arose and diversified from these prokaryotic antecedents. The discovery of ubiquitin, E1-like, E2-like and small-RING finger (srfp) protein components in the Aigarchaeota and the Asgard archaea superphyla has provided a substantive step toward addressing this evolutionary question. Encoded in operons, these components are likely representative of the progenitor apparatus that founded the modern eukaryotic ubiquitin modification systems. Here we report that these proteins from the archaeonCandidatus 'Caldiarchaeum subterraneum ' operate together as a bona fide ubiquitin modification system, mediating a sequential ubiquitylation cascade reminiscent of the eukaryotic process. Our observations support the hypothesis that complex eukaryotic ubiquitylation signalling pathways have developed from compact systems originally inherited from an archaeal ancestor. In eukaryotic cells, the ubiquitylation system regulates several cellular processes central to protein homoeostasis. Here the authors demonstrate the existence of an eukaryotic-like ubiquitylation cascade requiring E1, E2 and E3-like enzymes in the archaeonC. subterraneum, shedding light on the evolution of the ubiquitin-proteasome system.